Self-Improvement Plan as a Science Entrepreneur Through Social Media Optimization: Perspective of Female Pre-service Science Teachers - Laelasari, Iseu (Education, Science, and Technology International Conference, 2025)
This research aims to determine the perspective of pre-service science teachers regarding self-improvement plans as a science-entrepreneur through social media optimization. Researchers used a qualitative descriptive method with a total of 45 female pre-service science teacher participants enrolled as students of the 6th semester. The main instrument in this research is an open questionnaire containing 16 questions to express interest and entrepreneurship plans, the main profession after graduation, business management, the use of social media, and the effectiveness of it self. The findings showed that 95.6% of pre-service science teachers were interested in entrepreneurship, 88.9% of them had plans for entrepreneurship. There are two categories of entrepreneurs preference identified, namely science entrepreneurs (58.14%) and science edupreneurs (41,86%). Most of the participants (77.8%) planned to run the teaching profession as the main profession and entrepreneurship as a side profession, 17.8% planned to make entrepreneurship as the main profession. The output of assignments in lectures on several subjects such as development of science learning media, science teaching materials, science project, STEM, Biomimicry, science entrepreneurship, science edupreneurship, and halal product science also influence students' interest in entrepreneurship. Instagram (100%) and TikTok (93,02%) were chosen as the most widely preference social media. All participants view that social media is more effective and efficient because it has more advantages compared to conventional methods.